Mechanisms and advantages of natural derived small molecule compounds in the prevention and treatment of colorectal cancer: a review - Liao, Ming-Jie; Dong, Hao-Yu; Chen, Gang; Li, Wei-Wei; Li, Guo-Feng (Frontiers in Pharmacology, 2025)
Globally, colorectal cancer (CRC) ranked third in cancer prevalence and emerged as the primary contributor to cancer-related fatalities in 2022, with projections indicating substantial escalation by 2040. The malignant progression of healthy colonic cells involves complex interactions among multiple cellular pathways over extended periods (typically exceeding 10 years), influenced by dietary patterns, lifestyle factors, and genetic predispositions. In addition, marked disparities in CRC incidence and mortality appear to show large differences across geographic regions, demographic groups, and biological sexes, suggesting that there are traces of CRC. Therefore, timely intervention or regression of the development of CRC, particularly targeting high-risk populations, may be an excellent strategy to reduce CRC burden in forthcoming decades. Natural derived small molecule compounds (NDSMCs) exhibit significant advantages, including structural diversity, unique biological activities, low toxicity and multi-target effects. Increasing evidence suggests that NDSMCs demonstrate therapeutic potential against CRC through multi-target mechanisms, such as modulation of gut microbiota, induction of ferroptosis, and regulation of programmed cell death pathways (apoptosis/autophagy), thereby offering promising avenues for CRC treatment. However, comprehensive reviews in this field remain scarce. Consequently, this study systematically summarizes the research advancements over the past 5 years regarding the mechanisms of NDSMCs in combating CRC, aiming to provide valuable insights for therapeutic strategies, preventive measures, and novel drug development. Furthermore, the clinical progress and limitations of certain NDSMCs in CRC treatment are also discussed.